Experimental thermal degradation analysis of pentaerythritol with alumina nano additives for thermal energy storage application. (April 2019) - Venkitaraj, K.P.; Suresh, S.
Graphical abstract: Highlights: Thermal degradation kinetic study of a solid –solid phase change material using non-isothermal TGA. The effect of adding Al2 O3 nanoparticles on thermal degradation of pentaerythritol is studied. The activation energy of the alumina enhanced pentaerythritol is calculated using isoconversional method- KAS. The degradation rate of pentaerythritol was found to be increasing with increase in weight fraction of Al2 O3 nanoparticles. Abstract: The present work investigates the effect of addition of Al2 O3 nanoparticles on thermal degradation kinetics of pentaerythritol (PE), a solid-solid phase change material, using a Thermogravimetry analyzer. For this TGA experiments were conducted using PE added 0.1% and 1% weight fractions of Al2 O3 nanoparticles at heating rates of 5 °C/min, 10 °C/min, 20 °C/min, 40 °C/min under non-isothermal conditions. This paper presents the application of isoconversional (model free) method Kissinger–Akahira–Sunose (KAS) for estimation of activation energy of the samples from the non-isothermal TGA data. The average activation energy of PE, PE + 0.1% Al2 O3 and, PE + 1% Al2 O3 were found to be 123, 116, & 98 kJ/mol respectively. It was understood from the kinetic analysis that the addition of Al2 O3 nanoparticles resulted in lowering the activation energy of pentaerythritol.